Triple nanocomposites of CoMn2O4, Co3O4 and reduced graphene oxide for oxidation of aromatic alcohols - Jha, Ajay; Mhamane, Dattakumar; Suryawanshi, Anil; Joshi, Sameer M.; Shaikh, Parvez; Biradar, Narayan S.; Ogale, Satishchandra; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2014)
A composite of reduced graphene oxide (RGO) with oxides of manganese and cobalt together was prepared by a solvothermal method. During synthesis, both the reduction of graphene oxide as well as the growth of nanorod shaped CoMn2O4 and Co3O4 occurred simultaneously having a crystallite size of similar to 8 nm calculated from X-ray diffraction (XRD). The as-obtained triple nanocomposite material designated as RGO-MnCoO exhibited excellent activity for the liquid phase aerobic oxidation of aromatic alcohols under base-free conditions selectively giving the corresponding aldehydes (>85%). RGO loading was varied in the range of 1-10%, among which 1% RGO-MnCoO showed maximum catalytic activity enhancement of 24% as compared to the bare mixed oxide (MnCo-MO) for the oxidation of vanillyl alcohol. HR-TEM of RGO-MnCoO revealed that it was a composite material having uniform nanotubes of similar to 25 nm length and 6 nm diameter with a fringe pattern showing the (103) and (004) planes and lattice spaces of 0.26 nm and 0.22 nm, respectively, for the spinel CoMn2O4. The detailed studies on the morphology, size and composition of the as-prepared RGO-MnCoO nanocomposite by XRD, XPS, N-2-adsorption/desorption and O-2-TPD techniques were used to understand the role of RGO in the enhancement of catalytic activity for oxidation reaction.

Microwave-assisted synthesis of 5-substituted 1H-tetrazoles via [3+2] cycloaddition over a heterogeneous Cu-based catalyst: application to the preparation of N-13-labelled tetrazoles - Joshi, Sameer M.; Mane, Rasika B.; Pulagam, Krishna R.; Gomez-Vallejo, Vanessa; Llop, Jordi; Rode, Chandrashekhar (New Journal of Chemistry, 2017)
The [3+2] cycloaddition between various nitriles and sodium azide proceeds smoothly in the presence of a new Cu-II catalyst in N-methyl-2-pyrrolidone (NMP) to give the corresponding 5-substituted 1H-tetrazoles. The desired tetrazoles were obtained in high yields within 3-30 min by employing controlled microwave heating. The reaction most probably proceeds through the activation of the nitrile groups by the Cu-II species, followed by a successive [3+2] cycloaddition with the sodium azide. The good performance of the catalyst enabled the preparation of selected tetrazoles labelled with the positron emitter nitrogen-13 even under conventional heating. The short reaction time, simple work-up procedure, and recyclability of the catalyst are advantages of the method reported here.

Enolate-mediated regioselective synthesis of 1,2,3-triazoles via azide-aldehydes or ketones [3+2]-cycloaddition reactions in aqueous phase - Tripathi, Anupam; Rode, V, Chandrashekhar; Llop, Jordi; Chavan, Subhash P.; Joshi, Sameer M. (Tetrahedron Letters, 2020)
A synthetic route for the direct conversion of arylazides into the corresponding trizoles via phase transfer catalyst-assisted [3+2] cycloaddition reaction under basic conditions in aqueous medium is reported. This synthetic methodology, which offers high yields and excellent regioselectivity for varieties of triazoles at 100 degrees C for 24 h-48 h and this `greener' synthesis constitutes an alternative to the previously reported well established click reactions. Published by Elsevier Ltd.
Keywords: Azides plus aldehydes or ketones; Click chemistry; triazoles; Water